Moisture absorption properties of biomimetic laminated boards made from cross-linking starch/maize stalk fiber - Zhang, Fu; Wang, Wei; Tong, Jin; Zhou, Jiang (International Journal of Agricultural and Biological Engineering, 2015)
In the research, three kinds composite materials of biomimetic laminated boards made from cross-linking starch/maize stalk fiber—the single layer jute fiber reinforced maize stalk fiber boards, the dual layer jute fiber reinforced maize stalk fiber boards, the jute fiber hybrid reinforced maize stalk fiber boards were obtained according to the formulation of cross-linking maize starch adhesive and the preparation process of composite materials. The hygroscopicity variation of the biomimetic laminated boards made from cross-linking starch/maize stalk fiber was investigated under different relative humidity conditions. The moisture absorption rate and the variation velocity were used as important evaluation indexes to evaluate the moisture absorption properties of the straw fiber composites. The mathematical models of the moisture absorption rate and the variation velocity were established. The hygroscopicity variation curves of three kinds of composite materials were measured under the five different relative humidity conditions. The results showed that the three kinds composites had low moisture absorption rate compared with other stalk fiber composites which were good at water resistance and the waterproof property of the three kinds stalk fibers were excellent under the experimental conditions. The research provides a useful reference to improve the water resistance of fiber composites and a new idea on the development and application of the biodegradable composites, especially the straw fiber reinforced composites.Keywords: straw, stalk fiber, starch, composite, moisture absorption property, laminated boardsDOI: 10.3965/j.ijabe.20150802.1495